Combinatorial Recurrences and Linear Difference Equations - Jiménez, M. José; Encinas, Andrés M. (Electronic notes in discrete mathematics, 2016)
In this work we introduce the triangular arrays of depth greater than 1 given by linear recurrences, that generalize some well-known recurrences that appear in enumerative combinatorics. In particular, we focussed on triangular arrays of depth 2, since they are closely related to the solution of linear three–term recurrences. We show through some simple examples how these triangular arrays appear as essential components in the expression of some classical orthogonal polynomials and combinatorial numbers.